Analyzing the Implementation of Practicum Organic Compound Separation and Purification in the Chemistry Education Study Program - Khoirunnisa, Fitriah; Anwar, Sjaeful; Kadarohman, Asep; Hendrawan, ‎ (KnE Social Sciences, 2024)
Students acquire various skills in the laboratory through scientific development practices such as demonstrations and experiments. The primary objective of this study is to gather empirical data regarding the implementation of organic compound separation and purification techniques at tertiary educational institutions to examine their efficacy as a proactive step to facilitate ongoing educational endeavors. The elements discussed include the practicum topics completed, the organic chemistry instruments and equipment possessed, how the practicum is conducted, and the problems and their resolutions. This study’s respondents included course instructors, chemistry lab assistants, and students previously attending practicum content. This study used a qualitative research methodology to analyze multiple chemistry education study programs across various locations in Indonesia. Data collecting methods include open-closed surveys, observation, and documentation. The findings indicated that the separation and purification practicum topic incorporates concepts related to separation and purification, employing extraction, chromatography, distillation, sublimation, and recrystallization techniques. Some chemistry education programs needed adequate instrumentation for organic chemistry. In addition, the wet laboratory practicum for separating and purifying the studied organic compounds are yet to be completed as per the planned topics. Green chemistry and project-based learning have been largely implemented in the practicum, but the micro-scale concept, which can help reduce practicum waste, are yet to be implemented. Inadequate tools and materials for the practicum, as well as inadequate reference materials, are some of the obstacles that hinder the practicum’s efficiency. Hence, there is a want for pragmatic instruments that can effectively cater to the demands of ongoing education. This practicum set should facilitate using green chemistry and micro-scale, focusing on minimizing pollution that can harm the environment. Keywords: practicum organic, compound separation, purification, chemistry education